The Ragged Trousered Philanthropists - Japanese edition, 1971 (1971)
1971 "The Ragged Trousered Philanthropists - Japanese edition, 1971" [t0540.jpg], 1971 Japanese edition of 'The Ragged Trousered Philanthropists' translated by T. Hironaka (pen name Jun Murski) and published by Tam Shobo in 1971.